Pd-SnO2-SiO2 self-supporting flexible nanofiber membrane gas sensor for hydrogen detection and preparation method of Pd-SnO2-SiO2 self-supporting flexible nanofiber membrane gas sensor

The Pd-SnO2-SiO2 nanofiber membrane gas sensor, prepared by electrospinning and magnetron sputtering, solves the problems of insufficient high-temperature resistance and room-temperature performance of flexible gas sensors, and achieves high sensitivity and high selectivity for hydrogen detection, making it suitable for hydrogen monitoring in wearable devices.

CN121385046APending Publication Date: 2026-01-23SHAANXI NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511758303.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-27
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing flexible gas sensors rely on organic substrates, which have poor high-temperature resistance and insufficient room-temperature performance, making it difficult to meet the high breathability and high sensitivity detection requirements of wearable devices, especially in the non-invasive and real-time monitoring of hydrogen in human exhaled gas.

Method used

A substrate-free SnO2-SiO2 biphase nanofiber membrane was prepared by electrospinning, and Pd nanoparticles were deposited by magnetron sputtering. Combined with flexible printed Ag interdigitated electrodes, a self-supporting Pd-SnO2-SiO2 nanofiber membrane gas sensor was formed, achieving high sensitivity and high selectivity for hydrogen detection.

Benefits of technology

It achieves high response and good selectivity to hydrogen at room temperature, and has excellent air permeability and high temperature resistance. It is suitable for integrated hydrogen monitoring in wearable devices such as masks, and can adapt to high-performance detection in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121385046A_ABST
    Figure CN121385046A_ABST
Patent Text Reader

Abstract

The invention discloses a Pd-SnO2-SiO2 self-supporting flexible nanofiber membrane gas sensor for hydrogen detection and a preparation method of the Pd-SnO2-SiO2 self-supporting flexible nanofiber membrane gas sensor, and aims to solve the problems that an existing flexible gas sensor depends on an organic substrate and is poor in high temperature resistance and insufficient in room temperature performance. According to the sensor, an electrostatic spinning technology is adopted for preparing a double-phase nanofiber membrane with crystalline phase SnO2 as a framework and amorphous phase SiO2 as a filling agent, and self-supporting can be achieved without a flexible substrate; pd nanoparticles are deposited on the fiber membrane through magnetron sputtering, and an Ag interdigital electrode is printed. Wherein the crystal-amorphous double-phase structure not only endows the material with excellent flexibility and high air permeability, but also provides a rich gas reaction interface; due to the full-inorganic characteristic, the high-temperature-resistant performance is achieved. The sensor shows high sensitivity, high selectivity and good flexible stability to hydrogen at room temperature under the environment of 37 DEG C and 80% humidity, is suitable for detecting hydrogen exhaled by a human body through wearable equipment such as a mask, and provides a new scheme for the metal oxide flexible gas sensor.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of gas sensors, and particularly relates to a substrate-free, self-supporting flexible gas sensor capable of detecting hydrogen in a room-temperature high-humidity environment. BACKGROUND

[0002] In recent years, with the increasing application demand of wearable devices in the fields of medical health and environmental safety monitoring, higher requirements are put forward for the flexibility, portability and mechanical stability of gas sensors. Although semiconductor metal oxides (SMOs) are widely used in resistive gas sensors due to their excellent gas sensing characteristics, their inherent brittleness makes them difficult to be directly applied to flexible devices.

[0003] At present, the mainstream strategy to realize flexible gas sensors is to coat or build SMO sensing layers on organic flexible substrates such as polyimide. However, this method has significant limitations: first, the bonding force between the rigid SMO material and the flexible substrate is weak, and material shedding is easy to occur during repeated bending, leading to sensor performance degradation; second, the organic substrate usually has a dense structure, resulting in poor overall gas permeability of the sensor, which not only affects the wearing comfort, but also seriously hinders the diffusion of the target gas and the sensing efficiency; most importantly, the organic substrate has poor heat resistance and cannot withstand high-temperature processes, which fundamentally limits the possibility of optimizing the microstructure of the material and improving the performance of the sensor through high-temperature annealing, aging and other necessary means.

[0004] To overcome the above bottlenecks, some research has turned to the development of all-inorganic self-supporting sensors, such as using double spinning technology to prepare amorphous fiber substrates and mixed spinning sensing layers. Although this method improves the temperature resistance to some extent, its flexibility still depends on the fiber substrate as support, and the intrinsic flexibility of the sensing material, i.e. single SMO nanofiber, is not achieved. In addition, the mixed spinning process easily leads to poor material continuity, resulting in high baseline resistance of the sensor, which brings challenges to the miniaturization and low-power integration of the device.

[0005] On the other hand, in the application aspect, non-invasive and real-time monitoring of hydrogen (H2) in human exhaled gas is of great significance for the diagnosis and management of diseases such as lactose intolerance. However, traditional detection methods rely on bulky equipment and are difficult to meet the needs of daily wearable monitoring. Therefore, developing a substrate-free sensor with intrinsic flexibility, high gas permeability, high temperature resistance and excellent gas sensing performance has become an urgent technical problem to be solved in this field. SUMMARY

[0006] The application aims to solve the technical bottlenecks of the existing flexible gas sensor, such as dependence on an organic substrate, poor high-temperature resistance and insufficient room-temperature performance, and provides a Pd-SnO2-SiO2 self-supporting flexible nanofiber membrane gas sensor with good air permeability and high-temperature resistance and high sensitivity and selectivity to H2 gas. Compared with the traditional method of coating a gas-sensitive material on a flexible substrate, the application uses electrospinning to prepare a self-supporting flexible SnO2-SiO2 dual-phase nanofiber membrane without a substrate, and deposits Pd nanoparticles on the flexible fiber membrane through magnetron sputtering, thereby realizing high response and good selectivity to H2 at room temperature without damaging the flexibility of the fiber membrane.

[0007] The Pd-SnO2-SiO2 self-supporting flexible nanofiber membrane gas sensor provided by the application is prepared by the following steps: Step 1: SnCl2 is dissolved in a mixed solvent of anhydrous ethanol and N,N-dimethylformamide, hydrochloric acid is added under stirring, then polyvinylpyrrolidone is added until complete dissolution, and finally tetraethyl orthosilicate is added and stirred uniformly to obtain a clear spinning precursor solution. The spinning precursor solution is loaded into a polypropylene syringe and installed on an electrospinning device to spin into a membrane. After spinning, the complete fiber membrane is removed and kept at 80-120 DEG C in air for 1-2 h, and then programmed to 500-800 DEG C for calcination for 1-2 h to obtain a flexible SnO2-SiO2 dual-phase nanofiber membrane.

[0008] Step 2: The above flexible SnO2-SiO2 dual-phase nanofiber membrane is placed in a magnetron sputtering chamber, and Pd is deposited on the fiber membrane by direct current magnetron sputtering. Subsequently, a DB100 software is used to design a suitable size of interdigital electrode pattern, and a flexible printing device is used to print Ag interdigital electrodes on the fiber membrane.

[0009] Further, in the above step 1, the volume ratio of the anhydrous ethanol and N,N-dimethylformamide is preferably 1:2-3:2.

[0010] Further, in the above step 1, the concentration of polyvinylpyrrolidone in the spinning precursor solution is preferably 5x10 -4 -9x10 -4 mol / L, the concentration of SnCl2 is 0.2-0.4 mol / L, the concentration of tetraethyl orthosilicate is 1.0-1.5 mol / L, and the concentration of HCl is 0.08-0.15 mol / L.

[0011] Further, in the step 1 above, during the electrospinning process, the receiver rotation speed is controlled to be 150-200 rpm, the working distance is 17-19 cm, the negative bias voltage is-2.0 to-2.5 kV, the positive bias voltage is 20.0-22.0 kV, and the chamber temperature is 45-60 °C. The flow rate of the spinning precursor solution is controlled to be 1.2-1.5 mL·h -1 .

[0012] Further, in the step 1 above, the obtained fiber membrane is preferably kept in air at 100-120 °C for 1-2 h, and then programmed to 500-600 °C for calcination for 1-2 h.

[0013] Further, in the step 1 above, the heating rate during the keeping in air is preferably 4-6 °C / min, and the heating rate during the calcination is preferably 1-3 °C / min.

[0014] Further, in the step 2 above, the magnetron sputtering deposition time is preferably 30-90 s, and the working current is 30-60 mA.

[0015] Further, in the step 2 above, the feeding gas pressure for the flexible printing is preferably 100-200 kPa.

[0016] The application also provides the use of the above-mentioned Pd-SnO2-SiO2 self-supporting flexible nanofiber membrane gas sensor in detecting hydrogen, which can also be integrated on a mask to detect H2 in human exhaled gas.

[0017] The beneficial effects of the application are as follows: This invention successfully fabricated a substrate-free, self-supporting SnO2-SiO2 crystalline-amorphous biphase nanofiber membrane using electrospinning technology. This unique structure utilizes crystalline SnO2 as a conductive framework to provide gas-sensing activity, while amorphous SiO2 uniformly fills the interphase spaces, acting as a "binder." The synergistic effect of these two phases at the nanoscale effectively releases stress through the viscous flow of the amorphous phase, imparting inherent flexibility to the material and avoiding the brittle fracture problem of traditional single-phase materials. It also creates abundant phase interfaces, providing numerous active sites for gas adsorption and reaction. Furthermore, by optimizing the Sn / Si ratio, flexibility and electrical properties are balanced. The introduction of SiO2 inhibits excessive SnO2 grain growth, enhancing flexibility and bringing the grain size closer to the Debye length, thus improving gas-sensing performance. The conductive percolation network formed by the SnO2 grains ensures good semiconductor properties. Subsequently, through an integrated process of magnetron sputtering deposition of Pd nanoparticles and flexible printing of Ag interdigitated electrodes, the sensor's gas-sensing response speed and selectivity to hydrogen are significantly improved without compromising the material's inherent flexibility. The resulting Pd-SnO2-SiO2 nanofiber membrane possesses all-inorganic properties, giving it excellent high-temperature resistance and opening up possibilities for subsequent high-temperature processing optimization. Its self-supporting structure and highly permeable nanofiber network perfectly meet the comfort and gas diffusion efficiency requirements of wearable devices. Experiments demonstrate that this sensor exhibits high sensitivity, high selectivity, and excellent flexibility and stability for hydrogen at 37℃ and 80% humidity, providing a high-performance solution for integrated hydrogen monitoring in flexible wearable devices such as masks, while also broadening its application prospects in high-temperature and complex environments. Attached Figure Description

[0018] Figure 1 These are SEM images of the flexible SnO2-SiO2 biphase nanofiber membranes prepared in Example 1 and Comparative Example 1, showing bending experiments.

[0019] Figure 2 This is a resistance-bending cycle diagram of the flexible gas sensors prepared in Example 1 and Comparative Example 1.

[0020] Figure 3 The figures show the gas-sensitive response curves of the flexible gas sensors prepared in Example 1 and Comparative Example 2 to 20 ppm H2 at 37 °C and 80% RH.

[0021] Figure 4 This is a comparison chart of the response values ​​of the flexible gas sensor prepared in Example 1 to H2 gas at a concentration of 20 ppm and other interfering gases.

[0022] Figure 5 This is the response of the flexible gas sensor prepared in Example 1 to different concentrations of H2.

[0023] Figure 6 Response stability of the flexible gas sensor prepared in Example 1 to 20 ppm concentration of H2 after different numbers of 140° bending. DETAILED DESCRIPTION

[0024] The application will be further described in detail below in conjunction with the accompanying drawings and examples, but the scope of protection of the application is not limited to these examples. Example 1

[0025] Step 1: 500 mg of stannous chloride dihydrate and 100 μL of 37% mass concentration hydrochloric acid were added to a mixed solvent of 5 mL of anhydrous ethanol and 5 mL of N,N-dimethylformamide, and after stirring vigorously for 10 min, 1.0 g of polyvinylpyrrolidone was slowly added under stirring until completely dissolved, and 0.308 g of tetraethyl orthosilicate was added after stirring for 1 h, and the clear spinning precursor solution was obtained after stirring for 12 h. The concentration of polyvinylpyrrolidone in the spinning precursor solution was 7.61×10 -4 mol / L, the concentration of stannous chloride was 0.32 mol / L, the concentration of tetraethyl orthosilicate was 0.15 mol / L, and the concentration of HCl was 0.12 mol / L. The spinning precursor solution was loaded into a polypropylene syringe and installed on an electrospinning device to spin into a film. During the electrospinning process, the receiver speed was controlled at 150 rpm, the working distance was 18 cm, the negative bias voltage was-2.1 kV, the positive bias voltage was 21 kV, the chamber temperature was 45 °C, and the flow rate of the spinning precursor solution was controlled at 1.2 mL·h -1 -1 by using a precision syringe pump. After spinning, the complete fiber film was removed and first heated to 120 °C at a heating rate of 5 °C / min in an air atmosphere, and then heated to 500 °C at a heating rate of 2 °C / min, and calcined for 1 h to obtain a flexible SnO2-SiO2 dual-phase nanofiber film.

[0026] Step 2: The above flexible SnO2-SiO2 dual-phase nanofiber film was placed in a magnetron sputtering cavity, and Pd was deposited on the fiber film by direct current magnetron sputtering, with the working current set at 30 mA and the deposition time set at 60 s. Subsequently, Ag interdigital electrodes were printed on the fiber film by a flexible printing device to obtain a flexible gas sensor.

[0027] Comparative Example 1 Step 1: The difference from Step 1 of Example 1 is that no tetraethyl orthosilicate is added, and the SnO2 nanofiber does not have self-supporting properties and is in the form of a powder.

[0028] Step 2: The SnO2 nanofiber powder above was coated on a commercial flexible PET electrode, and Pd was deposited on the flexible PET electrode by direct current magnetron sputtering, with a working current of 30 mA and a deposition time of 60 s, to prepare a flexible gas sensor.

[0029] Comparative Example 2 Step 1: The same as Step 1 of Example 1.

[0030] Step 2: The difference from Step 2 of Example 1 is that Pd nanoparticles are not deposited by magnetron sputtering, but Ag interdigital electrodes are directly printed on the flexible SnO2-SiO2 dual-phase nanofiber membrane by a flexible printing device to prepare a flexible gas sensor. Example 2

[0031] Step 1: 500 mg of stannous chloride dihydrate and 100 μL of 37% hydrochloric acid were added to a mixed solvent of 5 mL of anhydrous ethanol and 5 mL of N,N-dimethylformamide, and after stirring vigorously for 10 min, 1.0 g of polyvinylpyrrolidone was slowly added under stirring until completely dissolved, and 0.308 g of tetraethyl orthosilicate was added after stirring for 1 h, and stirring was continued for 12 h to obtain a clear spinning precursor solution. The concentration of polyvinylpyrrolidone in the spinning precursor solution was 7.61 x 10 -4 mol / L, the concentration of stannous chloride was 0.32 mol / L, the concentration of tetraethyl orthosilicate was 0.15 mol / L, and the concentration of HCl was 0.12 mol / L. The spinning precursor solution was loaded into a polypropylene syringe and installed on an electrospinning device to spin into a film. During the electrospinning process, the receiver speed was controlled at 200 rpm, the working distance was 18 cm, the negative bias voltage was -2.1 kV, the positive bias voltage was 21 kV, the chamber temperature was 50 °C, and the flow rate of the spinning precursor solution was controlled by a precision syringe pump at 1.2 mL·h -1 -1. After spinning, the complete fiber membrane was removed and first heated to 120 °C at a rate of 5 °C / min in an air atmosphere, and then heated to 600 °C at a rate of 2 °C / min, and calcined for 1 h to obtain a flexible SnO2-SiO2 dual-phase nanofiber membrane.

[0032] Step 2: The flexible SnO2-SiO2 dual-phase nanofiber membrane above was placed in a magnetron sputtering chamber, and Pd was deposited on the fiber membrane by direct current magnetron sputtering, with a working current of 30 mA and a deposition time of 60 s. Subsequently, Ag interdigital electrodes were printed on the fiber membrane by a flexible printing device to obtain a flexible gas sensor.

[0033] By Figure 1It can be seen that the flexible SnO2-SiO2 dual-phase nanofiber membrane prepared in Example 1 still maintains the complete structure on the surface without cracks after large-angle bending, indicating that the flexible SnO2-SiO2 dual-phase nanofiber membrane still maintains good flexibility after bending. Comparative Example 1 is to directly coat the powder sample which cannot be self-supported on the commercial PET, and many cracks appear on the surface after large-angle bending, which indicates that the flexible sensor prepared by this method has poor flexibility.

[0034] The flexible SnO2-SiO2 dual-phase nanofiber membrane prepared in Example 1 and the SnO2 nanofiber prepared in Comparative Example 1 were placed on a bending characterization instrument for bending cycles, and the results are shown in Figure 2 . The results show that after 100 times of bending, the baseline resistance of the flexible SnO2-SiO2 dual-phase nanofiber membrane prepared in Example 1 remains stable, and the resistance change ratio of each bending is 1.50%, which is completely acceptable for hydrogen sensing. After 100 times of bending, the baseline resistance of the SnO2 nanofiber prepared in Comparative Example 1 drifts seriously, and the resistance change ratio reaches 191.53%, which is too large to interfere with the response signal of gas sensing.

[0035] As can be seen from Figure 3 , the flexible gas sensor prepared in Comparative Example 2 has no response to 20 ppm H2 gas at 37 °C and 80% RH. However, the flexible gas sensor prepared in Example 1 shows obvious response characteristics under the same conditions, and its response value to 20 ppm H2 is as high as 1.81. In comparison, the H2 response performance of the flexible gas sensor prepared in Example 1 is obviously better than that of Comparative Example 2. This is mainly due to the fact that Comparative Example 2 does not use magnetic sputtering to sputter Pd nanoparticles. The addition of Pd nanoparticles can effectively promote the dissociation and overflow of hydrogen to the SnO2 surface, thereby enhancing the gas sensing performance.

[0036] As can be seen from Figure 4 , the flexible gas sensor prepared in Example 1 shows significant response to 20 ppm H2 gas at 37 °C and 80% RH, and its response value is much higher than that of the interfering gas (such as NH3, NO, CH4, etc.) under the same conditions. The results show that the sensor has good selectivity to H2, which is conducive to accurate detection in a complex gas environment.

[0037] In order to simulate the human exhaled gas environment, the test environment temperature was set to 37 °C and the humidity was set to 80% RH. From Figure 5As can be seen from Table 1, the response values of the flexible gas sensor prepared in Example 1 to H2 gas with concentrations of 7 ppm, 10 ppm, 20 ppm, 50 ppm and 100 ppm at 37 °C were 1.18, 1.33, 1.80, 3.07 and 4.76, respectively. The results show that the sensor still has excellent H2 gas sensing performance in a low-temperature and high-humidity environment.

[0038] From Figure 6 As can be seen from Table 2, the response values of the flexible gas sensor prepared in Example 1 to 20 ppm H2 gas after 0, 2000, 4000, 6000 and 8000 times of 140° bending were 1.81, 1.80, 1.82, 1.79 and 1.80, respectively. The results show that the sensor can still maintain stable gas response performance after multiple mechanical bending, further verifying its excellent mechanical flexibility and structural stability.

Claims

1. A method for preparing a Pd-Sn02-Si02 self-supporting flexible nanofiber membrane gas sensor, characterized by: The method comprises the following steps: Step 1: tin chloride is dissolved in a mixed solvent of anhydrous ethanol and N,N-dimethylformamide, hydrochloric acid, polyvinylpyrrolidone and tetraethyl orthosilicate are sequentially added under stirring to obtain a clear spinning precursor solution; the spinning precursor solution is electrospun into a film, the obtained fiber film is kept at 80-120 °C in air for 1-2 h, and then is calcined at a programmed temperature of 500-800 °C for 1-2 h to obtain a flexible SnO2-SiO2 dual-phase nanofiber film; Step 2: Pd is deposited on the flexible SnO2-SiO2 dual-phase nanofiber film by magnetron sputtering, and Ag interdigital electrodes are flexibly printed on the fiber film.

2. The method for preparing a Pd-Sn02-Si02 self-supporting flexible nanofiber membrane gas sensor according to claim 1, characterized in that: In step 1, the volume ratio of the anhydrous ethanol and N,N-dimethylformamide is 1:2-3:

2.

3. The method for preparing a Pd-Sn02-Si02 self-supporting flexible nanofiber membrane gas sensor according to claim 1, characterized in that: In step 1, the concentration of polyvinylpyrrolidone in the spinning precursor solution is 5 x 10 -4 ~ 9 x 10 -4 mol / L, the concentration of stannous chloride is 0.2~0.4 mol / L, the concentration of tetraethyl orthosilicate is 1.0~1.5 mol / L, and the concentration of HCl is 0.08~0.15 mol / L.

4. The method for preparing a Pd-Sn02-Si02 self-supporting flexible nanofiber membrane gas sensor according to claim 1, characterized in that: In step 1, during the electrospinning process, the receiver rotation speed is controlled to be 150-200 rpm, the working distance is controlled to be 17-19 cm, the negative bias voltage is controlled to be -2.0 to -2.5 kV, the positive bias voltage is controlled to be 20.0-22.0 kV, the chamber temperature is controlled to be 45-60 °C, and the spinning precursor solution flow rate is controlled to be 1.2-1.5 mL·h -1 .

5. The method for preparing a Pd-Sn02-Si02 self-supporting flexible nanofiber membrane gas sensor according to claim 1, characterized in that: In step 1, the obtained fiber film is kept at 100-120 °C in air for 1-2 h, and then is calcined at a programmed temperature of 500-600 °C for 1-2 h.

6. The method for preparing a Pd-Sn02-Si02 self-supporting flexible nanofiber membrane gas sensor according to claim 1, characterized in that: In step 1, the heating rate for keeping in air is 4-6 °C / min, and the heating rate for calcination is 1-3 °C / min.

7. The method for preparing a Pd-Sn02-Si02 self-supporting flexible nanofiber membrane gas sensor according to claim 1, characterized in that: In step 2, the deposition time for magnetron sputtering is 30-90 s, and the working current is 30-60 mA.

8. The method for preparing a Pd-Sn02-Si02 self-supporting flexible nanofiber membrane gas sensor according to claim 1, characterized in that: In step 2, the feeding gas pressure for flexibly printing is 100-200 kPa.

9. A Pd-SnO2-SiO2 self-supporting flexible nanofiber film gas sensor prepared by the method of any one of claims 1-8.

10. Use of the Pd-SnO2-SiO2 self-supporting flexible nanofiber film gas sensor of claim 9 in detecting hydrogen.

Citation Information

Cited By

  • Hydrogen sensor based on modified polyimide fiber textile and preparation method thereof

    CN121678781A